Evanescent-wave Sensing with Multiple Sampling Channels along a Single Optical Fiber - Ma, Jianjun; Bock, Wojtek J. (Photonics Letters of Poland, 2013)
We demonstrate that the evanescent-wave sensing platform with one sampling channel may be expanded to at least a 12-channel system. These channels are implemented as a series of 2-mm long exposed segments of the fiber core sidewall along a single optical fiber. Using the cladded fiber segments as channel separations, we achieve a condition of zero inter-channel crosstalk, which is fundamental to the system operation, for both 4- and 12-channel systems. Theoretical interpretation of the mechanism of zero inter-channel crosstalk is examined in detail. Full Text: PDF References C. R. Taitt, T. P. Anderson, and F. S. Ligler, "Evanescent wave fluorescence biosensors", Biosens. Bioelectron., 20, 2470 (2005). CrossRef R. Narayanaswamy and O. S. Wolfbeis, Optical Sensors: Industrial Environmental and Diagnostic Applications, Wolfbeis, O. S., Ed.; Springer: Germany, 2004. J. Ma and W. J. Bock, "Reshaping a sample fluid droplet: toward combined performance enhancement of an evanescent-wave fiber-optic fluorometer", Opt. Lett., 32, 8 (2007). CrossRef H. Chen, J. Ma, J. Chen, and W. J. Bock, "Significant retrieval of lost evanescent power by tuning modes close-to-cutoff with a gel-coated taper", Opt. Lett., 36, 2092 (2011). CrossRef J. Ma, Y. Chiniforooshan, J. Chen, W. J. Bock, W. Hao, and Z. Y. Wang, "Recapturing lost evanescent power by tuning end face total internal reflection capable tunneling modes at a roughened fiber end face", Opt. Lett., 36, 3581 (2011). CrossRef D. Gloge, "Weakly Guiding Fibers", Appl. Opt., 10, 2252 (1971). CrossRef